Antibacterial Activity Test of (Peperomia pellucida L.) Extract against Streptococcus sanguinis - Ula, Ulfatul; Zuraidah, Zuraidah; Hidayat, Muslich; Hanim, Nafisah; Emalfida, Emalfida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Streptococcus sanguinis is a type of bacteria that plays a role in dental plaque development. Sirih cina (Peperomia pellucida L.) is recognized for having secondary metabolites that may have antibacterial effects. This study aims to determine the content of secondary metabolites and the effectiveness of sirih cina extract in inhibiting the growth of Streptococcus sanguinis. The investigation utilized the disk diffusion method with six different treatments and three repetitions. Results were assessed using a one-way ANOVA along with Duncan’s test at a significance level of 5%. The phytochemical analysis revealed that sirih cina extract (Peperomia pellucida L.) has alkaloids, flavonoids, saponins, tannins, polyphenols, and steroids. Tests showed that the extract successfully stopped the growth of Streptococcus sanguinis at all tested concentrations. The concentration of 1000 mg/mL showed the greatest inhibition zone size of 10.33 mm, while the positive control had an inhibition zone of 10.83 mm, showing moderate inhibition. A one-way ANOVA indicated an F-value of 13.145 with a significance of p < 0.001, and Duncan’s test showed that the 500 mg/mL, 750 mg/mL, and 1000 mg/mL concentrations were as effective as the positive control. Therefore, the extract (Peperomia pellucida L.) shows promise as a natural antibacterial agent against Streptococcus sanguinis.